Network Flow Integration to Improve Generalization of Machine Learning-Based IDS - Santos, Kelson Carvalho; Miani, Rodrigo Sanches (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2026: Anais do XXVI Simpósio Brasileiro de Cibersegurança, 2026)
The growth of cyber threats and the evolution of attacks highlight the need for more robust machine learning-based IDS capable of operating in heterogeneous, dynamic network environments. Although some approaches presented in the literature improve the performance of these systems, their generalization capability remains limited in multi-domain data scenarios. This paper investigates supervised domain adaptation through controlled integration of labeled target-domain flows to diversify training and reduce generalization performance degradation in IDS. Results show improvements in specific scenarios, depending on the integrated flow type, with trade-offs among attack detection, class balance, and false alarms.